Energy-based automatic determination of buffer region in the divide-and-conquer second-order Møller-Plesset perturbation theory - Fujimori, Toshikazu (Journal of computational chemistry, 2021)
© 2021 The Authors. Journal of Computational Chemistry published by Wiley Periodicals LLC.